2020
DOI: 10.1557/jmr.2020.175
|View full text |Cite
|
Sign up to set email alerts
|

Structure–processing relationships of freeze-cast iron foams fabricated with various solidification rates and post-casting heat treatment

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…
Figure 1 “Porous metals – from nano to macro”: figures reproduced from articles in this Focus Issue illustrate the range of pore size in porous metals. (a) scanning transmission electron micrograph of a nanoporous palladium - polymer composite membranes for separations and catalysis; the nanoporous Pd was prepared by the dealloying method 20 , (b) scanning electron microscope (SEM) micrograph of nanoporous copper prepared by dealloying 21 , (c) molecular dynamics simulations of crystalline copper nanoporous structures during tensile loading 22 – scale is provided by individual atoms visible in enlarged view in circles, (d) SEM micrograph of tensile section of a carbon nanotubes reinforced aluminum foam prepared by powder metallurgy 23 (e) three-dimensionally ordered porous tungsten (inverse opals structure), prepared by a templating method 24 (f) tomographic view of porous iron created by freeze casting, ice template removal and sintering 25 (g) a 3D printed Ti-6Al-4V gyroid-structured scaffold showing diagonal shear bands from compression tests 26 (h) X-ray tomographic reconstruction of open-channel aluminum fabricated by casting and subsequent extraction of lubricated metallic wires 27 28 (i) photographs of closed-cell aluminum foams with graded density before and after a compression test 29 (j) SEM micrographs of hierarchically-porous titanium with macro-/micro-/nanopores, prepared using NaCl spacer and dealloying methods 30 .
Figure 2 (a) Upward view of the Eiffel Tower in Paris, showing hierarchical structure of 18,000 iron parts (mostly struts) connected with 250 million rivets.
…”
Section: Pore Size Effectsmentioning
confidence: 99%
“…
Figure 1 “Porous metals – from nano to macro”: figures reproduced from articles in this Focus Issue illustrate the range of pore size in porous metals. (a) scanning transmission electron micrograph of a nanoporous palladium - polymer composite membranes for separations and catalysis; the nanoporous Pd was prepared by the dealloying method 20 , (b) scanning electron microscope (SEM) micrograph of nanoporous copper prepared by dealloying 21 , (c) molecular dynamics simulations of crystalline copper nanoporous structures during tensile loading 22 – scale is provided by individual atoms visible in enlarged view in circles, (d) SEM micrograph of tensile section of a carbon nanotubes reinforced aluminum foam prepared by powder metallurgy 23 (e) three-dimensionally ordered porous tungsten (inverse opals structure), prepared by a templating method 24 (f) tomographic view of porous iron created by freeze casting, ice template removal and sintering 25 (g) a 3D printed Ti-6Al-4V gyroid-structured scaffold showing diagonal shear bands from compression tests 26 (h) X-ray tomographic reconstruction of open-channel aluminum fabricated by casting and subsequent extraction of lubricated metallic wires 27 28 (i) photographs of closed-cell aluminum foams with graded density before and after a compression test 29 (j) SEM micrographs of hierarchically-porous titanium with macro-/micro-/nanopores, prepared using NaCl spacer and dealloying methods 30 .
Figure 2 (a) Upward view of the Eiffel Tower in Paris, showing hierarchical structure of 18,000 iron parts (mostly struts) connected with 250 million rivets.
…”
Section: Pore Size Effectsmentioning
confidence: 99%
“…Sublimation of the frozen solvent produces a porous structure. Initially, sublimation freezing was used to make highly porous ceramics, but recently this method has also been applied to metal suspensions such as titanium [ 7 , 8 ], Ti-Al alloy [ 9 ], iron [ 10 , 11 , 12 ], copper [ 13 , 14 , 15 , 16 ], nickel foams [ 17 , 18 , 19 ] and Cu-Ni [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is also costeffective, eco-friendly, and scalable on an industrial level. However, pure Fe-foams, manufactured by FC using water [26] and camphene-based [27,28] hematite slurries, have shown significant modification of the pore structure after being subjected to several redox cycles. Authors have found a continuous reduction in the pore size due to the sintering of the Fe cell walls, which is especially critical when initial pore sizes are under 30 μm in diameter.…”
Section: Introductionmentioning
confidence: 99%